Penerapan Model Pembelajaran Project Based Learning (PjBL) Berbantuan Media Visual untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V SD N 1 Penatih Tahun Pelajaran 2019/2020 - I Wayan Darmayoga; I Ketut Suparya (Edukasi: Jurnal Pendidikan Dasar, 2021)
This study aims to determine the use of Project Based Learning (PjBL) methods support by visual media could increase the interest and learning achievements of science in fourth grade students of Elementary School number 1 Penatih in the academic year 2019/2020. The method of collecting data that used to this research is the test methods of collecting data on student learning achievements. Based on the result of research could explain the average percentage of student learning achievements of Social Science increased to 40% and the classical completeness increased to 30%. The use of Project Based Learning (PBL) methods support by visual media in the first cycle the average percentage of students' learning interest increased to 60%, and classical completeness reached 50%. With the improvement in cycle II the average percentage of interest in learning increased to 80%, and the classical completeness reached 85%. Keywords: Project Based Learning (PjBL)methods, visual media, learning achievements